Differences in outcomes of newly diagnosed acute myeloid leukemia for adolescent/young adult and younger patients. Issue 23 (19th September 2013) - Canner, Jason; Alonzo, Todd A.; Franklin, Janet; Freyer, David R.; Gamis, Alan; Gerbing, Robert B.; Lange, Beverly J.; Meshinchi, Soheil; Woods, William G.; Perentesis, John; Horan, John
<x xml:space="preserve">Abstract</x> BACKGROUND Studies comparing survival of adolescent and young adult (AYA) patients to that of younger patients with newly diagnosed acute myeloid leukemia (AML) have yielded conflicting results. In order to more accurately characterize relative survival and other outcomes of AYA patients, a cross‐study analysis was conducted using data from recent trials conducted by the Children's Cancer Group (CCG) and Children's Oncology Group (COG). METHODS Data were combined from the CCG‐2891, CCG‐2941, CCG‐2961, and AAML03P1 trials. The data set included 1840 patients, comprising 238 AYA and 1602 younger patients. RESULTS Overall survival was not significantly different in the 2 groups (AYA, 49% ± 7% versus younger, 54% ± 3% (± 2 standard errors), P = .058). Relapse was lower in AYA patients (30% ± 7% versus 41% ± 3%, P = .002), but treatment‐related mortality (TRM) was higher (25% ± 6% versus 12% ± 2%, P < .001). After adjustment for other factors, older age remained strongly associated with TRM (hazard ratio = 2.30, 95% CI = 1.59‐3.33, P < .001). Infection accounted for the excess TRM in AYA patients. CONCLUSIONS Survival in AYA and younger patients with newly diagnosed AML is similar; however, older patients are at higher risk for TRM. More effective strategies for preventing mortality from infection in AYA patients are needed. Cancer 2013;119:4162–4169. © 2013 American Cancer Society.